A clinical study on trial of labor after caesarean at tertiary care centre - Desai, Riddhi N.; Modi, Prerak R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The global rise in caesarean section (CS) rates has led to an increase in women eligible for Trial of Labor After Caesarean (TOLAC). TOLAC Offers an Opportunity for Vaginal birth After Caesarean (VBAC), thereby reducing complications of repeat caesarean sections. Methods: This prospective Observational Study was conducted on 50 antenatal women with a history of one prior lower segment caesarean section (LSCS) at civil hospital, B J medical College, Ahmedabad from September 2023 to December 2023. The women were assessed based on eligibility and monitored during labor. The study analyzed outcomes based on prior caesarean indication, previous vaginal delivery, and intrapartum events. Results: Out Of 50 women, 32 (64%) achieved successful VBAC, 18 (36%) underwent emergency LSCS for fatal distress (44.44%), scar tenderness (27.77%), non-progression of labor (22.22%), and uterine rupture (5.55%). Prior vaginal delivery had a strong association with successful VBAC (80%). Conclusions: TOLAC is a viable and safe option for with a prior LSCS if they are carefully selected and monitored. The best predictors for success are prior vaginal delivery, and a non-recurrent indication in previous caesarean. Institutional delivery is essential for ensuring maternal and fetal safety.